Teacher Strategies in Developing Students' Critical Thinking Skills - Wulandari, Fenita Mei; Meganesia, Vinardita; Oktavia, Adella Dewi; Agustina, Melda Dwi; Pebrian, Melina; Tsania, Jihan Zahra; Cahyaningtyas, Andarini Permata (Transpublika Publisher, 2025)
This study aims to describe teacher strategies in developing critical thinking skills of fifth grade students at SDN Wonolopo 02, Semarang. This study was motivated by the results of initial observations which showed that learning was still carried out conventionally and centered on the teacher, resulting in low student engagement and learning outcomes. This study used a descriptive qualitative method with data collection techniques in the form of questionnaires and interviews involving students, class teachers, and principals. Data validity was obtained through source triangulation to obtain comprehensive and credible results. The results showed that teachers had implemented various strategies, such as managing learning time, sequencing learning activities, selecting media, and implementing student-based learning methods such as Problem-Based Learning (PBL) and Project-Based Learning (PJBL). This strategy supports the development of critical thinking indicators such as interpretation, analysis, evaluation, and inference. Although there are still some obstacles in its implementation, the results of the interview showed an increase in students' critical thinking skills. In conclusion, the implementation of PBL and PJBL with the right strategy can improve students' critical thinking skills, especially with collaborative support between teachers and schools.